LEVEL OF AWARENESS OF MICROPLASTICS AMONG GENERATION Z - Singh, Harpreet; Kumar, Raj; Singh, Chef. Jaswinder (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Though Generation Z’s understanding level is unknown, microplastics have grown to be a major environmental and public health issue. This study aims to evaluate their knowledge of microplastics by means of analysis of their understanding of sources, environmental and health effects, and preventive measures. Using a mixed-method approach including surveys and interviews, we investigate Generation Z’s knowledge of microplastics and whether this awareness leads to proactive behavior. The results expose notable knowledge gaps; social media is the main source of information found here. Though they come across material on microplastics, many of them have poor understanding of their long-term consequences and environmentally friendly solutions. This paper underlines the need of including microplastic education into curriculum of schools, improving online literacy to fight false information, and supporting policies-oriented awareness campaigns. Through bettering educational initiatives and encouraging active engagement, we might help Generation Z to adopt sustainable practices and support more strong environmental laws.